Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VIII SMP Negeri 15 Padang - Gina Silvia; Armiati Armiati (Universitas Ma'arif Lampung, 2026)
This study aims to describe the development of mathematical problem-solving skills among students learning through the discovery learning model and to analyze whether the mathematical problem-solving skills of students learning through the discovery learning model are better than those of students learning through the direct instruction model in the eighth grade at State Junior High School 15 Padang. The study was conducted using a quantitative approach through a quasi-experimental method employing a posttest-only control group design. Data were collected through quizzes and a final test, then analyzed using descriptive and inferential statistics. The results showed that the mathematical problem-solving skills of students in the experimental class improved across all indicators during the implementation of the discovery learning model. Descriptively, the average final test score for the experimental class was 60.50, while that for the control class was 51.12. The results of the Mann–Whitney test showed a significance value of 0.007, so H0 was rejected. Thus, students who learned using the Discovery Learning model had better mathematical problem-solving skills compared to those who learned using the direct instruction model in eighth grade at State Junior High School 15 Padang.